ORGANISATIONAL CULTURE RESEARCH IN COMPETITIVE SPORT - A SYSTEMATIC REVIEW - Tamás NAGY; Tamás LACZKÓ; Dávid PAÁR (Cluj University Press, 2024)
Introduction: Defining and measuring organisational culture in the sport sector receives little attention. Nevertheless, it has an impact on the effectiveness and functioning of sport organisations. Objective: The aim of this paper is to explore definitions of sport organisational culture and to present its measurement possibilities through international literature. Methods: The secondary research will review the international literature on competitive sport between 1999 and 2022, using a systematic sampling according to predefined criteria. Results: In addition to general bibliometric data, the results present the frequency of keywords for each definition, the measurement methods used to assess sport culture, and group studies on sport culture according to the literature. Conclusion: We discuss the results of the publications presented in the literature and their conclusions, thus contributing to the Hungarian research on sport culture. Received 2024 January 13; Revised 2024 February 21; Accepted 2024 February 22; Available online 2024 March 15; Available print 2024 March 15.